A study of students' perception of online learning classes based on mars model in UiTM Seremban 3 Campus / Muhammad Akif Zakwan Amir, Abdul Hakim Mat Luwi and Farah Adilla Ab Rahman - Amir, Muhammad Akif Zakwan; Mat Luwi, Abdul Hakim; Ab Rahman, Farah Adilla (2021)
Online learning is a type of learning that uses Internet tools while avoiding face-to-face interaction with lecturers (Allam et al., 2020). Online learning is often referred to as e-learning, blended learning, virtual learning, and distance learning (Allam et al., 2020). Online learning is defined as having access to learning activities via technology (Moore et al., 2011). Online learning has recently grown in popularity to deliver education and information to students (Dash, 2019). The growth of the Internet enables online learning and teaching, which substantially impacts the quality of teaching and learning (Zhao, 2003). It also has an impact on the rise of online learning (Willett et al., 2019). According to Zhao (2003), there are several advantages to online learning and teaching, including the ability for students to have more flexibility in terms of time, place, and pace. Furthermore, online learning lowers the cost of education while also encouraging students and teachers to learn more and faster. However, online learning may fall short of specific colleges' quality standards (Zhao, 2003). A face-to-face class is a learning environment where students receive direct instruction from their teachers (Novak, 1998). According to a study by Bali and Liu (2018), online learning is preferable since it saves money and gives students more flexibility in terms of time and space. On the other hand, face-to-face classes provide pupils with a higher level of satisfaction than online learning. When it comes to professors, they prefer face-to-face sessions since students are more engaged than online learning (Ali et al., 2020). Following the closure of numerous buildings, including schools and colleges, due to the Coronavirus illness (COVID-19) pandemic, online learning and teaching became the primary mode of instruction (Carter et al., 2020). Universiti Teknologi Mara (UiTM) used several technologies such as I-learn, Google Classroom, and Skype to perform blended learning (Allam et al., 2020). Microsoft Teams and U-Future are two other platforms used by UiTM (a platform made by the university). Students at UiTM must learn, study, and complete the lecture session without physically being present in the classroom. Students and lecturers may not be able to prepare for the shift from face-to face classrooms to online learning and teaching methods because lecturers lack expertise and abilities in delivering education online (Ali et al., 2020).